Interactive music therapy : a positive approach : music therapy at a child development centre - Oldfield, Amelia (Jessica Kingsley Publishers, 2006)
In Interactive Music Therapy & ndash; A Positive Approach, Amelia Oldfield explains how her approach to music therapy sessions establishes a constructive musical dialogue with children that emphasises positive experiences & ndash; these establish trust and allow feelings to be expressed through music. Describing the general benefits of this approach, the author also details its application for specific clinical groups including children with autistic spectrum disorders, relationship difficulties or physical disabilities. Individual chapters focus specifically on child development issues and in c.